Students’ Self-Confidence and Mathematics Learning Outcomes Using the Student Teams Achievement Division (STAD) Cooperative Learning Model in Grade VIII of SMP N 1 Sasak Ranah Pasisia, West Pasaman Regency - Zolanda Anggraini; Isnaniah; M. Imamuddin; Tasnim Rahmat (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study was motivated by problems found in Grade VIII of SMP N 1 Sasak Ranah Pasisia, West Pasaman Regency, namely the low self-confidence of students in learning. This could be seen during the teaching and learning process, where only a few students took the initiative to present their work in front of the class. Students’ low mathematics learning outcomes were also evident from their daily test scores. The research problems in this study were: (1) how students’ self-confidence develops during the learning process using the cooperative learning model of the Student Teams Achievement Division (STAD) type, and (2) whether students’ mathematics learning outcomes taught using the STAD cooperative learning model are better than those taught using conventional learning. This research employed a pre-experimental approach with the Static Group Comparison Design. The sample was determined randomly after conducting tests of normality, homogeneity, and equality of means on the population data. The sample consisted of students from class VIII.2 as the experimental group and class VIII.1 as the control group. Students’ self-confidence data were collected through a questionnaire, while learning outcomes were obtained from a test administered to students. Based on the results of the analysis, the percentage of students’ self-confidence was 76.18%, categorized as high. The mathematics learning outcome test was analyzed using the t-test at a significance level of α = 0.05, yielding tcount > ttable (2.96 > 1.67) and P-value = 0.008 < α = 0.05. Therefore, H0 was rejected and H1 was accepted. It can be concluded that students’ mathematics learning outcomes using the STAD cooperative learning model are better than those using conventional learning in Grade VIII of SMP N 1 Sasak Ranah Pasisia, West Pasaman Regency.